KERJASAMA NEGARA ANGGOTA ASEAN DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN HUTAN DI INDONESIA BERDASARKAN ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION - Yolanda Dwi Maharany; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Transboundary haze problem that occurred in the ASEAN region has been prominent since the 1980s. Due to the increasing number of forest fires that transboundary haze from year to year, then in 2002 all ASEAN members agreed to establish an international agreement on transboundary haze namely the ASEAN Agreement on Transboundary Haze Pollution. In this agreement are several provisions on cooperation will be carried out by member states in agreement on the prevention and control of forest fires that occurred in the ASEAN region. In this study the authors specialize in the area of Indonesia. The purpose of this thesis, namely; First, to determine the cooperation of ASEAN member countries in the prevention and control of forest fires in Indonesia based on the ASEAN Agreement On Transboundary Haze Pollution. Second, to determine the responsibility of the state polluters against forest fires that occurred in the ASEAN region by the ASEAN Agreement on Transboundary Haze Pollution.Based on the results of research and discussion the authors described above, there are several important things, first cooperation ASEAN Member Countries In Prevention And Mitigation Forest Fire In Indonesia based ASEAN Agreement On Transboundary Haze Pollution can be seen in the fourth chapter, namely Article 4 paragraph ( 1) and (2), Article 9, Article 12, paragraph (1) and (2) and Article 16 paragraph (1). Second, Responsibility of the State Pollutant Against Forest Fires Happened in ASEAN region by the ASEAN Agreement on Transboundary Haze Pollution which each party is responsible to ensure that activities within their jurisdiction and control do not cause damage to the environment and endanger human health. In addition, the polluters are required to provide exemptions and facilities that need to the donor. These exceptions include a waiver of taxes, duties or other charges levied on the equipment and materials brought in for the purpose of providing assistance.Keyword: Cooperation of ASEAN Member States - Fires - Asean Agreement On Transboundary Haze Pollution